Numerical investigation of micro-structural influence on stress distribution in heat affected zone of a welded joint - Elisaveta Doncheva (SCIENTIFIC ASSOCIATION FOR DEVELOPMENT AND AFFIRMATION OF NEW TECHNOLOGIES, 2015)
The preliminary motivation for this paper is numerical investigation of stress distribution in heat affected zones of welded joints. The micro-structural complexity of the characteristic zones increase the difficulty in investigating the relationship between micro-structural morphologies and mechanical properties. In order to investigate this relationship, several 2D numerical models are constructed with randomly obtained grain boundaries and grains with different shapes, sizes and components. The Voronoi tessellation is used to represent the microstructures and the finite element calculation is conducted on the ABAQUS computing platform after the finite element simulation model is built up. The construction of representative volume elements (RVE), material characterization, meshing techniques and boundary conditions used in numerical models are described in detail. The interpretation of the results obtained from the numerical models are graphically displayed and analyzed. Results show that stress value and distribution within different zones is related to grains orientation and the orientation of its neighboring grains. Furthermore, the numerical investigations show that definition of material characteristics on grain level is extremely important in order to simulate accurate results. The differences between mechanical properties obtained in models with fine-grained and coarse-grained microstructure lead to conclusions that grain boundaries greatly affect stress and deformation distributions.
Keywords: welded joints, microstructure, RVE, Voronoi